Revision notes for the final FRCR Part A - Mankad, Kshitij; Hoey, Edward T. D. (JP Medical, 2010)
Summarises the core knowledge required for each of the six systems based modules included in the exam, all in highly succinct bullet point format. Each chapter has been authored by recent exam candidates and in turn edited by sub-specialty radiologists to provide highly relevant, high quality, high yield revision notes.